Disseminated annular granuloma: a rare dermatological manifestation of diabetes - Patiño-Orellana, Claudia F.; Vázquez Donoso, Pablo X.; Andraca, Irlanda Ríos (International Journal of Research in Medical Sciences, 2024)
Granuloma annulare (GA) is a benign granulomatous dermatosis of unknown etiology. In adults, the most common clinical form is the localized variant, characterized by a non-scaly, erythematous violaceous ring-shaped plaque, followed by the disseminated form that predominantly affects the trunk and limbs. It has been associated with diabetes mellitus, dyslipidemia, and autoimmune disorders. Herein, we present a 70-year-old patient who is overweight and has hepatic steatosis, with lesions of confirmed disseminated annular granuloma through histopathology and a subsequent diagnosis of type 2 diabetes.